The Radical Historicity of the Human Being in Ernesto de Martino’s Work: The Crisis of Presence and Cultural Apocalypses - Rivera García, Antonio (Estudios de Filosofía, 2016)
To Ernesto de Martino, understanding the radical historicity –contingency– of the human being involves, in the first place, studying the wide foundations of philosophic anthropology, the ethos of trascendimento, the valorising energy that makes it possible to go beyond the biological state and access cultural life. Secondly, it involves reflecting on the ever-present risk of losing the abovementioned ethos. When this risk affects the individual, we can talk about an existential crisis; and when it affects the society or culture as a whole, we can talk about a cultural apocalypse. This risk tends to be concealed not only by mythical and religious thinking but also by the history of philosophy. De Martino has thought of an alternative to this act of masking, that he calls umanesimo storicistico, which converges with an ethnographic humanism that integrates histories of a multiplicity of cultures. Finally, the distinction E. de Martino makes between a cultural apocalypse with eschaton, referred to the end of ’’a’’ world, and without eschaton, or related to the end of ’’the’’ world is analysed. This second modality of apocalypse or cultural crisis is especially pathologic; a reflection on its terrible consequences is made at the end of the article.